Answer:
f(x) + g(x) = 2x² - 5x - 8 ⇒ 2nd answer
Explanation:
* Lets explain how to solve the problem
- We can add to functions by adding the like terms in them
∵ f(x) = 2x² + 3x - 4
- f(x) is a quadratic function because the greatest power of x is 2
∵ g(x) = -8x - 4
- g(x) is a linear function because the greatest power of x is 1
∵ f(x) + g(x) means (f + g)(x)
∴ f(x) + g(x) = (2x² + 3x - 4) + (-8x - 4)
- Add the like terms
∵ 3x + -8x = -5x
∵ -4 + -4 = -8
∴ f(x) + g(x) = 2x² + -5x + -8
- Remember (+)(-) = (-)
∴ f(x) + g(x) = 2x² - 5x - 8
* f(x) + g(x) = 2x² - 5x - 8